2018
DOI: 10.5093/psed2018a2
|View full text |Cite
|
Sign up to set email alerts
|

¿Aplican los Alumnos las Estrategias de Aprendizaje que Afirman Aplicar? Control de la Comprensión en Textos Expositivos

Abstract: En este trabajo se evalúan las estrategias declaradas en el autoinforme y el control de la comprensión lectora (metacomprensión) en una prueba con textos científicos breves manipulados en 118 alumnos de educación secundaria en Madrid. El objetivo de esta investigación es verificar el grado de correlación entre lo declarado por cada alumno y el desempeño real ejecutado en la prueba. Los resultados evidencian una asociación significativa, aunque baja. De las once subescalas valoradas según lo que los alumnos dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…In contrast with what was expected, no relationship was found between higher reported use of strategies and better performance in tests to evaluate reading competence. These results are in line with other research (Jiménez-Taracido & Manzanal, 2018;Ruffing, Wach, Spinath, Brünken, & Karbach, 2015). This could be because of a difference between what is reported and real behaviour, or to misuse of the metacognitive strategies by the subjects (Winnie & Jamieson-Noel, 2003).…”
Section: Metacognitive Strategies Used and Reading Competencesupporting
confidence: 92%
“…In contrast with what was expected, no relationship was found between higher reported use of strategies and better performance in tests to evaluate reading competence. These results are in line with other research (Jiménez-Taracido & Manzanal, 2018;Ruffing, Wach, Spinath, Brünken, & Karbach, 2015). This could be because of a difference between what is reported and real behaviour, or to misuse of the metacognitive strategies by the subjects (Winnie & Jamieson-Noel, 2003).…”
Section: Metacognitive Strategies Used and Reading Competencesupporting
confidence: 92%
“…Similarly, Lewis and Mensink (2012) showed that participants devoted increased first-pass and look-back fixation time to question-relevant sentences in response to questions presented prior to reading, which in turn led to improved memory for information contained in question-relevant sentences. Moreover, taking into account some complementary and current studies, there can be also shown additional applications of the results reported in our study, as reading instructions and elaborative interrogation could facilitate the comprehension of visual narrative in a coherence/incoherence paradigm (Martín-Arnal et al, 2019), to improve strategies to comprehension in expository texts (Fonseca et al, 2019;Jiménez-Taracido & Manzanal-Martínez, 2018), as selfquestion to improve metacomprehension skills (León, Martínez-Huertas, et al, 2019), and to improve writing and oral summaries (Martínez-Huertas et al, 2018).…”
Section: Article In Presssupporting
confidence: 59%
“…Future studies should include more follow-up questions to better understand what students wanted to say. Moreover, participants’ strategies were self-reported, which is a limitation in itself because students can declare strategies they did not use, as Jiménez-Taracido and Manzanal-Martínez (2017) discovered. This reality inherent to the interview process highlights that having a clear portrait of strategic thinking is challenging and that even robust studies will only open windows on the complexity of participants’ thought processes.…”
Section: Discussionmentioning
confidence: 99%